Subtle leakage of a Majorana mode into a quantum dot - Vernek, E.; Penteado, P. H.; Seridonio, A. C. [UNESP]; Egues, J. C. (American Physical Society (APS), 2014)
We investigate quantum transport through a quantum dot connected to source and drain leads and side coupled to a topological superconducting nanowire (Kitaev chain) sustaining Majorana end modes. Using a recursive Green's-function approach, we determine the local density of states of the system and find that the end Majorana mode of the wire leaks into the dot, thus, emerging as a unique dot level pinned to the Fermi energy εF of the leads. Surprisingly, this resonance pinning, resembling, in this sense, a Kondo resonance, occurs even when the gate-controlled dot level εdot(Vg) is far above or far below εF. The calculated conductance G of the dot exhibits an unambiguous signature for the Majorana end mode of the wire: In essence, an off-resonance dot [εdot(Vg)≠εF], which should have G=0, shows, instead, a conductance e2/2h over a wide range of Vg due to this pinned dot mode. Interestingly, this pinning effect only occurs when the dot level is coupled to a Majorana mode; ordinary fermionic modes (e.g., disorder) in the wire simply split and broaden (if a continuum) the dot level. We discuss experimental scenarios to probe Majorana modes in wires via these leaked/pinned dot modes. © 2014 American Physical Society.